Deep assessment process : Objective assessment process for unilateral peripheral facial paralysis via deep convolutional neural network - Guo, Zhe-Xiao; Shen, Minmin; Duan, Le; Zhou, Yongjin; Xiang, Jianghuai; Ding, Huijun; Chen, Shifeng; Deussen, Oliver; Dan, Guo (My University, 2017)
Unilateral peripheral facial paralysis (UPFP) is a form of facial nerve paralysis and clinically classified according to facial asymmetry. Prompt and precise assessment is crucial to the neural rehabilitation of UPFP. For UPFP assessment, most of the existing assessment systems are subjective and empirical. Therefore, an objective assessment system will help clinical doctors to obtain a prompt and precise assessment. Distinguishing precisely between degrees of asymmetry is hard using pure pattern recognition methods. Thus, a novel objective assessment process based on convolutional neuronal networks is proposed in this paper that provides an end-to-end solution. This method could alleviate the problem and produced a classification accuracy of 91.25% for predicting the House-Brackmann degree on a given UPFP image dataset.
Keywords: Unilateral peripheral facial paralysis, objective assessment process, deep convolutional neural network, House-Brackmann facial nerve grading system; 004